2007
DOI: 10.1038/sj.cgt.7701021
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumor growth in vivo by in situ secretion of bispecific anti-CEA × anti-CD3 diabodies from lentivirally transduced human lymphocytes

Abstract: Infiltrating T lymphocytes are found in many malignancies, but they appear to be mostly anergic and do not attack the tumor, presumably because of defective T-cell activation events. Recently, we described a strategy for the tumor-specific polyclonal activation of tumor-resident T lymphocytes based on the in situ production of recombinant bispecific antibodies (bsAbs) by transfected nonhematological cell lines. Here, we have constructed a novel HIV-1-based lentiviral vector for efficient gene transduction into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 21 publications
(26 reference statements)
0
56
0
Order By: Relevance
“…In fact, we have previously shown that human T lymphocytes, transduced ex vivo to secrete the aCEA/aCD3 diabody in autocrine manner, inhibited the growth of CEA-positive tumors. 8 However, the short life span of activated human T lymphocytes and their inefficient transduction constitute important drawbacks for their application in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, we have previously shown that human T lymphocytes, transduced ex vivo to secrete the aCEA/aCD3 diabody in autocrine manner, inhibited the growth of CEA-positive tumors. 8 However, the short life span of activated human T lymphocytes and their inefficient transduction constitute important drawbacks for their application in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…11 Early passage HUVECs were transduced at a vector multiplicity of infection of 10, with lentivirus encoding the aCEA/aCD3 diabody and enhanced green fluorescent protein (EGFP) (Lenti dAb ), or with a lentivirus harboring a luciferase-IRES-EGFP cassette (Lenti Luc ). 7,8 More than 90% of transduced HUVEC (HUVEC dAb and HUVEC Luc ) expressed EGFP for at least 30 days in vitro ( Figure 1a) and showed normal morphology, phenotype and function (data not shown). Interestingly, the secretion of functional aCEA/aCD3 diabody molecules remained stable during this period with levels around 100 ng ml À1 per 10 5 cells per 72 h at day 30 (Figure 1b).…”
Section: Transduction Of Human Endothelial Cells With a Lentiviral Vementioning
confidence: 99%
See 3 more Smart Citations